2008
DOI: 10.1292/jvms.70.11
|View full text |Cite
|
Sign up to set email alerts
|

L-Ascorbic Acid Enhances Apoptosis in Human Gastric Carcinoma Cell Line AZ-521 Cells Infected with Mycoplasma hyorhinis

Abstract: ABSTRACT. Mycoplasma hyorhinis (M. hyorhinis) exerts multiple effects on cell metabolisms including apoptosis mediated by their endonucleases and nitric oxide production in vitro. Although AsA is preferable to health in general because of its reactive oxygen species scavenging activity, we found that in a human carcinoma cell line AZ-521 infected with M. hyorhinis, apoptosis was enhanced by addition of L-ascorbic acid (AsA) to the cell cultures. No significant differences were evident between the AZ-521 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Our preliminary examination suggested marked down-regulation of E-cadherin expression in AZ521 cells infected with M. hyorhinis based on a microarray analysis (unpublished data). Therefore, we hypothesized that excessive NO produced by M. hyorhinis infection leads to anoikis in AZ-521 cells.We previously reported that apoptosis in human carcinoma cell line AZ-521 infected with M. hyorhinis was enhanced by addition of L-ascorbic acid (AsA) to the cell cultures [21]. Since M. hyorhinis infection and/or AsA addition enhance iNOS activity [20], we proposed a hypothesis that M. hyorhinis infection results in the presence of another external apoptotic pathway including the NO pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary examination suggested marked down-regulation of E-cadherin expression in AZ521 cells infected with M. hyorhinis based on a microarray analysis (unpublished data). Therefore, we hypothesized that excessive NO produced by M. hyorhinis infection leads to anoikis in AZ-521 cells.We previously reported that apoptosis in human carcinoma cell line AZ-521 infected with M. hyorhinis was enhanced by addition of L-ascorbic acid (AsA) to the cell cultures [21]. Since M. hyorhinis infection and/or AsA addition enhance iNOS activity [20], we proposed a hypothesis that M. hyorhinis infection results in the presence of another external apoptotic pathway including the NO pathway.…”
mentioning
confidence: 99%
“…We previously reported that apoptosis in human carcinoma cell line AZ-521 infected with M. hyorhinis was enhanced by addition of L-ascorbic acid (AsA) to the cell cultures [21]. Since M. hyorhinis infection and/or AsA addition enhance iNOS activity [20], we proposed a hypothesis that M. hyorhinis infection results in the presence of another external apoptotic pathway including the NO pathway.…”
mentioning
confidence: 99%
“…With regard to the effects of vitamin C in cancer cells, it is known that it acts as an antioxidant at physiological levels and it could be linked to pro-oxidant effects at pharmacological doses which promote the death of cancer cells (Chen et al 2005 , 2007 ). Various in vitro studies have already shown that high concentrations of vitamin C led to apoptosis of cancer cells (Chen et al 2005 ; Ha et al 2009 ; Harakeh et al 2007 ; Hong et al 2007 ; Kim et al 2012 ; Obara and Harasawa 2008 ). So far, several mechanisms have been described in vitro which give a more detailed insight into the molecular pathways which contribute to the induction of apoptosis (Irimie et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CPF and lead have been shown to increase the production of free radical and decrease the availability of antioxidant molecules that mitigate the resultant damage. Vitamin C is a low-molecular weight antioxidant molecule that protects the cellular compartment from hydrophilic oxygen-nitrogen radicals; a property that makes it an efficacious antioxidant of the hydrophilic phase [23,24]. Earlier studies have shown the ability of vitamin C to mitigate toxicity induced by CPF [1,14,16,19,25] and lead [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%